Relational ambivalence: Exploring the social and discursive dimensions of ambivalence—The case of Turkish aging labor migrants. (February 2019) - Palmberger, Monika
Many of Vienna's labor migrants who entered Austria as so-called "guest workers" together with their spouses long nurtured the dream of returning to their country of origin, at the latest when they retired. By then, however, returning became less than straightforward leading to ambivalence regarding questions of belonging/return and transnational mobility and late-life care. Based on rich qualitative data, in this article, I show that ambivalences are found in the complexity of migrants' narratives, particularly in the way they (1) reassess past choices, (2) negotiate feelings of belonging, and (3) assess future options for late life and care. I argue that the social dimension of ambivalence, which I term "relational ambivalence, " is crucial to understanding the labor migrants' experiences, reflections, and choices. The analysis shows that ambivalence must be understood as a product of relationships rather than solely an individual experience. The concept of relational ambivalence captures these social and discursive dimensions of ambivalence. The article ultimately carves out the particularity of ambivalence in the general context of migration and in the specific context of Vienna's labor migrants, while accepting feelings of ambivalence or the simultaneity of different, opposing positions in one and the same person as a core human experience.